IDENTIFYING NON VALUE ADDED ACTIVITIES USING VALUE STREAM MAPPING TO REDUCE WASTE IN THE PVC CEILING INDUSTRY - Rita Aprilia; Grita Supriyanto Dewi; Ibnu Abdul Rosid (Journal of Industrial and Mechanical Engineering, 2026)
Production processes in the manufacturing industry still include activities that do not add value and could reduce productivity. This situation was observed in the PVC ceiling production process at PT XYZ, where production targets have not been fully met due to waste in the process flow. This study aims to identify non value added (NVA) activities and formulate process improvement proposals using the Lean Manufacturing approach with the Value Stream Mapping (VSM) method. The research was conducted through direct observation in the production area, interviews with relevant parties, and the collection of company data covering process flow, cycle time, waiting time, and transportation activities. The initial phase of the study began with creating a SIPOC diagram to provide an overview of the business process, followed by current-state mapping to categorize activities into VA, NVA, and NNVA. The mapping results revealed that the production process is still dominated by NNVA activities, particularly waiting time, repetitive transportation, and inconsistent application of work procedures. Based on these findings, improvement proposals were developed, focusing on waste reduction, material handling optimization, and SOP development. The results of this study are expected to assist the company in gradually and sustainably improving production process efficiency.